2012
DOI: 10.1007/s00125-012-2745-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the enteroviral capsid protein VP1 in the islet cells of patients with type 1 diabetes is associated with induction of protein kinase R and downregulation of Mcl-1

Abstract: Aims/hypothesis Immunohistochemical staining reveals that the enteroviral capsid protein VP1 is present at higher frequency in the insulin-containing islets of patients with recent-onset type 1 diabetes than in controls. This is consistent with epidemiological evidence suggesting that enteroviral infection may contribute to the autoimmune response in type 1 diabetes. However, immunostaining of VP1 is not definitive since the antibody widely used to detect the protein (Clone 5D8/1) might also cross-react with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
132
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(148 citation statements)
references
References 28 publications
15
132
0
1
Order By: Relevance
“…If so, it would be consistent with emerging data showing that low-level, persistent enteroviral infections can be detected in the peripheral blood of other recently diagnosed patients (8). Importantly, when IFN signature and low-level infection are considered together with evidence that a low-level, noncytolytic, persistent enteroviral infection of b-cells occurs in pancreata from cohorts in Italy (9), the U.K. (10,11), and the U.S. (network of pancreatic organ donors, nPOD) (11), one can envision a scenario where a primary acute viral infection leads to a secondary long-term persistent pancreatic infection that could ultimately drive the development of disease.…”
supporting
confidence: 79%
“…If so, it would be consistent with emerging data showing that low-level, persistent enteroviral infections can be detected in the peripheral blood of other recently diagnosed patients (8). Importantly, when IFN signature and low-level infection are considered together with evidence that a low-level, noncytolytic, persistent enteroviral infection of b-cells occurs in pancreata from cohorts in Italy (9), the U.K. (10,11), and the U.S. (network of pancreatic organ donors, nPOD) (11), one can envision a scenario where a primary acute viral infection leads to a secondary long-term persistent pancreatic infection that could ultimately drive the development of disease.…”
supporting
confidence: 79%
“…Upon exposure to 'danger signals' (e.g. viral infection or other exogenous or endogenous mediators that remain to be determined; [10,36,42,43]), production and release of type I IFNs (IFNα/β) is triggered in beta cells and neighbour cells, exerting both autocrine and paracrine effects. IFNα binds to the IFNAR1 and activates the type I IFN pathway, in which the TYK2-STAT2-IRF9 axis plays a critical role.…”
Section: Discussionmentioning
confidence: 99%
“…A number of viruses have been implicated, but the majority view suggests that one or more enteroviruses are the most likely candidates [1,2]. However, this evidence remains largely circumstantial and relies on a body of epidemiological data supported by immunohistochemical studies conducted with pathological specimens recovered from patients diagnosed with type 1 diabetes [1,[3][4][5]. These have revealed that a minority of islet cells of individuals with recentonset disease (and some with longer-duration illness) display evidence of enteroviral antigen expression [3][4][5].…”
Section: Introductionmentioning
confidence: 99%